2018
DOI: 10.3390/rs10101668
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Light Aircraft-Based Hyperspectral and Colour-Infrared Imaging to Identify Deciduous Tree Species in an Urban Environment

Abstract: One may consider the application of remote sensing as a trade-off between the imaging platforms, sensors, and data gathering and processing techniques. This study addresses the potential of hyperspectral imaging using ultra-light aircraft for vegetation species mapping in an urban environment, exploring both the engineering and scientific aspects related to imaging platform design and image classification methods. An imaging system based on simultaneous use of Rikola frame format hyperspectral and Nikon D800E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…From trees detected in CHM derived from high-resolution RGB data, 90%-97% were correctly classified as pine, spruce, birch, or larch. The use of hyperspectral imagery for identification of deciduous tree species reports also Mozgeris et al [181]. The study compared several machine learning classifiers, the best of which achieved the accuracy of 51%-72% for six deciduous species.…”
Section: Species Classificationmentioning
confidence: 83%
“…From trees detected in CHM derived from high-resolution RGB data, 90%-97% were correctly classified as pine, spruce, birch, or larch. The use of hyperspectral imagery for identification of deciduous tree species reports also Mozgeris et al [181]. The study compared several machine learning classifiers, the best of which achieved the accuracy of 51%-72% for six deciduous species.…”
Section: Species Classificationmentioning
confidence: 83%
“…It is obvious, that the private forest owner possessing several hectares of forest may not pay for remotely sensed data acquisition missions, even though they are very cheap solution based on e.g. the use of unmanned aviation vehicles or ultra-light aviation (Mozgeris & Augustaitis, 2013;Mozgeris et al, 2018a;Mozgeris et al, 2018b). Thus, availability of open source data opens additional opportunities for private forest inventories and management planning, even though the data may be not perfectly emulating the conventional orthophotos.…”
Section: Resultsmentioning
confidence: 99%
“…We collected hyperspectral imagery of each flight area using the Rikola HSI (Senop Oy, Oulu, Finland) hyperspectral camera. The Rikola HSI camera collects spectra for each pixel within the range of 500-900 nm with 16 programmable bands for any increment within that range (Mozgeris et al, 2018a). For this study, we used a band combination from 550-849 nm (~20 nm increments).…”
Section: Unoccupied Aerial System Flightsmentioning
confidence: 99%
“…Images acquired from the flights were pre-processed using the camera manufacturer software. Noise and vignetting were removed for image clarity, and digital number values (DN) were converted to radiance (W/(m 2 x srad x µm)) (Jakob et al, 2017;Mozgeris et al, 2018a). The Rikola HSI software aligns each image, but we found that the imagery had too much shift in between each band for the images to align properly (Mozgeris et al, 2018b).…”
Section: Unoccupied Aerial System Flightsmentioning
confidence: 99%